Tantangan Aktualisasi Zuhud di Era Society 5.0 - Fadlillah, Fadlillah; Wasil, Nurahmad (Journal of Islamic Education and Pedagogy, 2025)
The era of Society 5.0 has brought significant changes to various aspects of human life through the integration of digital technology and the physical world. However, this progress also presents challenges in maintaining spiritual values, such as zuhud, which emphasizes simplicity and a balance between worldly and spiritual matters. Amidst the growing trends of materialism and individualism, the values of zuhud remain relevant as moral guidance. This study aims to analyze the challenges, opportunities, and strategies for actualizing the values of zuhud in the Society 5.0 era. It is conducted due to the limited research linking the concept of zuhud with the context of modern technological revolutions. Using a qualitative approach based on literature review, the research seeks to provide practical and contextual solutions to various spiritual issues in the digital age. The research method involves content analysis of various literature, interviews with scholars, and observations of community practices that apply the values of zuhud. The findings reveal that the main challenges include pressures of a consumerist lifestyle and dependency on technology. However, the values of zuhud can be integrated through spirituality-based education, community roles, and the utilization of technology for good. These findings offer practical guidelines for maintaining a balance between spiritual and worldly life amidst the complexities of Society 5.0.